Climate warming mediates negative impacts of rapid pond drying for three amphibian species. Issue 4 (1st April 2014) - O'Regan, Sacha M.; Palen, Wendy J.; Anderson, Sean C.
Abstract : Anthropogenic climate change will present both opportunities and challenges for pool‐breeding amphibians. Increased water temperature and accelerated drying may directly affect larval growth, development, and survival, yet the combined effects of these processes on larvae with future climate change remain poorly understood. Increased surface temperatures are projected to warm water and decrease water inputs, leading to earlier and faster wetland drying. So it is often assumed that larvae will experience negative synergistic impacts with combined warming and drying. However, an alternative hypothesis is that warming‐induced increases in metabolic rate and aquatic resource availability might compensate for faster drying rates, generating antagonistic larval responses. We conducted a mesocosm experiment to test the individual and interactive effects of pool permanency (permanent vs. temporary) and water temperature (ambient vs. +∼3°C) on three anurans with fast‐to‐slow larval development rates (Great Basin spadefoot [ Spea intermontana ], Pacific chorus frog [ Pseudacris regilla ], and northern red‐legged frog [ Rana aurora ]). We found that although tadpoles in warmed pools reached metamorphosis 15–17 days earlier, they did so with little cost (<2 mm) to size, likely due to greater periphyton growth in warmed pools easing drying‐induced resource competition. Warming and drying combined to act antagonistically on early growth ( P = 0.06) and survival ( P = 0.06), meaning the combined impact was less than the sum of the individual impacts. Warming and drying acted additively on time to and size at metamorphosis. These nonsynergistic impacts may result from cotolerance of larvae to warming and drying, as well as warming helping to offset negative impacts of drying. Our results indicate that combined pool warming and drying may not always be harmful for larval amphibians. However, they also demonstrate that antagonistic responses are difficult to predict, which poses a challenge to proactive conservation and management. Our study highlights the importance of considering the nature of multiple stressor interactions as amphibians are exposed to an increasing number of anthropogenic threats.